The effectiveness of a counseling program in reducing emotional deprivation in children (Raparin Journal of Humanities (RJH), 2023)
This research aims to identify the effectiveness of a counseling program in reducing feelings of emotional deprivation among children. To achieve the objectives of the study, the researcher used a quasi-experimental approach, and the study sample consisted of (24) children who were randomly distributed to the experimental group (12) and the control group (12). The researcher prepared a measure of emotional deprivation consisting of three dimensions (psychological, social or relationship status, cognitive). The method of apparent honesty, and the stability was measured using three methods, the first (retest) with a value of (0.88) for the emotional deprivation scale, the second (Alfa Cronbach) and the value of stability was (0.86) by the Alpha Cronbach method, and third, the researcher extracted a proven value in a way (splitting midterm) and its value was (0.82 The researcher reached the following results:.1- There are no statistically significant differences between the average scores of the experimental and control groups in the pre-test and post-test of emotional deprivation.2- There are no statistically significant differences between the average scores of the experimental and control groups in the pre and post tests in the emotional deprivation scale according to the age group variable.3 - concluded that the counseling program had an effect in reducing emotional deprivation among children in favor of the experimental group, so the researcher presented some recommendations and suggestions.